The Wolf: The Last Remnants of the age of Sail in Southern Oman. (2nd January 2022) - Staples, Eric; Weismann, Norbert; Dziamski, Piotr; Ghidoni, Alessandro; Haar, Lilli; Vosmer, Tom
ABSTRACT: This article looks at a specific southern Arabian sailing vessel named the Wolf ( al-Dhi'b ), in order to better understand the life of a coastal trader on the southern Arabian coast that lived in the last days of commercial sail. Vessels such as the Wolf carried local products such as sardines, abalone and frankincense to northern Oman and Yemen, returning with dates and necessary foodstuffs shipped to Aden from India and East Africa. The article examines the remains of the Wolf, based on data from multiple documentation surveys, in conjunction with information gained from oral history interviews in order to highlight the central role that vessels such as the Wolf played in the maritime economic and social networks of the region.